ANALISIS GEOMORFOLOGI TERHADAP BENCANA BANJIR DI NAGARI TARAM KECAMATAN HARAU - Glory Muzdalifah; Ernawati Ernawati (JURNAL BUANA, 2021)
The purpose this research is to analyze the flood disaster in Nagari Taram Kecamatan Harau using a geomorphological approach. Data colllection techiques wiith map analysis, interview field observation as supporting data. The analysis technique used is descriptive quntitative with map overlay and scoring. The result showed that (1) the type of flood that occurred in Nagari Taram was the river overflow with the type of inundation for days. Flood disaster occues once a year in Nagari Taram. (2) The index of flood hazard in Nagari Taram is categorized as medium with an area of 2760.2 Ha. (3) Nagari Taram is a lowland and hilly area that has a varied topography, namely flat, hilly, undulating and has an altitude of 500 mdpl-1500 mdpl. The slopes in Nagari Taram are dominated by flat slopes ranging from 0-8% with an area of 1464.4 Ha. Keywords : geomorphological, Flood Disaster